Pregnancy outcomes in in vitro fertilization in 17-alpha-hydroxylase deficiency - Annika van Oosbree, M.S.-IV; Ayesha Asif, O.M.S.-IV; Sarah Hmaidan, O.D; Alan DeCherney, M.D (Elsevier, 2023)
Since the first case of 17-alpha-hydroxylase-deficiency (17-OHD) was described in 1966, a number of cases have been reported with a clinical picture of hypertension, hypokalemia, and hypogonadism. Infertility is a major concern for some of these individuals. This mini-review aims to detail the components of this disorder that affect fertility and focus on the recent acceleration in the success of achieving live births, as well as highlight the unsuccessful attempts. The data supporting successful live births remains limited, but existing evidence suggests that in vitro fertilization can be used in conjunction with hormone replacement therapy and steroid suppression to achieve live birth in patients with infertility from 17-OHD.